THE CONGREGATION FOR THE DOCTRINE OF THE FAITH’S CUM SANCTISSIMA AND QUO MAGIS DECREES OF FEBRUARY 22, 2020: A CANONICAL ANALYSIS OF THE DOCUMENTS CONCERNING THE NEW FORMULARIES OF THE SAINTS AND PREFACES IN THE LITURGY OF 1962 - Dawid Pietras (Forum Teologiczne, 2023)
The Congregation for the Doctrine of the Faith issued two documents concerning the liturgy of the Latin Church on February 22, 2020. These are general decrees about the liturgy of 1962, previously known as the extraordinary form of the Roman Rite, approved in forma communi by Pope Francis on December 5, 2019. It was the end of the Pontifical Commission Ecclesia Dei’s work which had been erected in 1988. According to these decrees, during liturgical celebrations, it is possible to use seven new prefaces ad libitum and to honor the Saints who have been introduced into the current Calendarium Romanum. The issued decrees are part of the process of mutual enrichment between the earlier liturgical tradition and the liturgy introduced after the Second Vatican Council.